A rural, community-based suicide awareness and intervention program - Jones, S.; Walker, C.; Miles, A.; De Silva, E.; Zimitat, Craig (Australian Rural Health Education Network, 2015)
Suicide is a prominent public health issue in rural Australia and specifically in Tasmania, which has one of the highest suicide rates in the country. The Community Response to Eliminating Suicide (CORES) program was developed in rural Tasmania in response to a significant number of suicides over a short period of time. CORES is unique in that it is both a community-based and gatekeeper education model. CORES aims to build and empower communities to take ownership of suicide prevention strategies. It also aims to increase the individual community member's interpersonal skills and awareness of suicide risks, while building peer support and awareness of suicide prevention support services within the community itself. Pre- and post-test surveys after the CORES 1-day suicide awareness and intervention program (SAIP) showed significant increases in levels of comfort and confidence in discussing suicide with those who may be contemplating that action. CORES builds community capital through establishing new connections within communities. Establishment of local executive groups, funding and SAIP are key activities of successful CORES programs in communities around Australia. Over half of the initial leaders are still actively involved after a decade, which reflects positively on the quality and outcomes of the program. This study supports CORES as a beneficial and feasible community-based suicide intervention program for rural communities.